Overview of Capacity Development at ILRI - Dror, Iddo (International Livestock Research Institute, 2015)
As part of an internal ‘capacity development’ week at the International Livestock Research Institute (ILRI) in December 2015, the institute presented different aspects of this work. In this video, Iddo Dror, head of the Capacity Development Unit, outlines the range of capacity development activities taking place throughout ILRI.